2008
DOI: 10.1038/sj.bjc.6604783
|View full text |Cite
|
Sign up to set email alerts
|

KRAS or BRAF mutation status is a useful predictor of sensitivity to MEK inhibition in ovarian cancer

Abstract: This study examined the status of KRAS and BRAF mutations, in relation to extracellular signal-regulated protein kinase (ERK) activation in 58 ovarian carcinomas to clarify the clinicopathological and prognostic significance of KRAS/BRAF mutations. Somatic mutations of either KRAS or BRAF were identified in 12 (20.6%) out of 58 ovarian carcinomas. The frequency of KRAS/BRAF mutations in conventional serous high-grade carcinomas (4.0% : 1/25) was significantly lower than that in the other histological type (32.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
74
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 36 publications
8
74
0
1
Order By: Relevance
“…Profound growth inhibition and apoptosis were observed in CI-1040-treated ovarian cancer cells with mutations in either KRAS or BRAF, compared with ovarian cancer cells containing wild-type KRAS/BRAF. 39 Although KRAS-mutated lung cancers, which comprise 20-30% of non-small cell lung cancers, are known not to respond to targeted therapies, recently it was shown that the combination of PI3K and MEK inhibitors may be a very potent combination in the treatment of KRAS-mutated lung cancers. When mouse models of lung cancer driven by mutant KRAS were treated with a combination of pan-PI3K, a mammalian target of rapamycin inhibitor, and an MEK inhibitor, there was marked synergy in shrinking these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Profound growth inhibition and apoptosis were observed in CI-1040-treated ovarian cancer cells with mutations in either KRAS or BRAF, compared with ovarian cancer cells containing wild-type KRAS/BRAF. 39 Although KRAS-mutated lung cancers, which comprise 20-30% of non-small cell lung cancers, are known not to respond to targeted therapies, recently it was shown that the combination of PI3K and MEK inhibitors may be a very potent combination in the treatment of KRAS-mutated lung cancers. When mouse models of lung cancer driven by mutant KRAS were treated with a combination of pan-PI3K, a mammalian target of rapamycin inhibitor, and an MEK inhibitor, there was marked synergy in shrinking these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…9 Meanwhile, these variants are the active subjects of clinical trials with MEK inhibitors in ovarian cancers. 29 Similarly, the p.Val600Glu variant of BRAF is druggable in melanoma, 12,30,31 whereas recent evidence indicates its potential predictive utility in colorectal cancer patients treated with EGFR inhibitors. 32 Figure 3 shows in further detail how sequence variants were classified for each of the four primary sites of cancer in our study.…”
Section: Resultsmentioning
confidence: 99%
“…The results of a phase III study have demonstrated that GSK1120212 is associated with a significant improvement in progression-free survival and overall survival, compared with chemotherapy, in patients with V600E or V600K BRAF-mutated advanced melanoma (23). Several studies have shown that KRAS and/ or BRAF mutations are associated with the sensitivity to MEK inhibitors in melanoma, thyroid cancer, colon cancer, and ovarian cancer (23)(24)(25)(26)(27). However, very limited information is available about the somatic MEK1 mutations in human malignancies.…”
Section: Discussionmentioning
confidence: 99%